Relationship Between Confidence and Self-Image with Social Media Use Intensity Instagram in Youth - Livianty, Safira; Darmawi, Yulia (International Journal of Social Science, Education, Communication and Economics, 2024)
This research was aimed at finding out the relationship between self-confidence and self-image with the intensity of using Instagram social media. The subjects in this research were teenagers who actively used social media Instagram as many as 105 people. The data collection tool used is the self-confidence scale, self-image scale and the intensity scale of Instagram social media use compiled with the linkert technique. The self-confidence scale has a reliability coefficient of 0.831, the self-image scale has a reliability coefficient of 0.817 and the intensity scale of using Instagram has a reliability coefficient of 0.829. Based on the results of data analysis through multivariate analysis, the correlation coefficient value is 0.680 with a sig value of 0.000, then there is a relationship between self-confidence, self-image and intensity of using Instagram.